Acoustic radiation force impulse of the liver after Fontan operation: Correlation with cardiopulmonary exercise test. (23rd February 2018) - Di Maria, Michael V.; Silverman, Lindsey; Younoszai, Adel K.; Meyers, Mariana L.; Capocelli, Kelley E.; Narkewicz, Michael R.
Abstract: Background: The current management paradigm for children with single ventricle heart disease involves a series of palliative surgeries, culminating in the Fontan operation. This physiology results in a high central venous pressure, and in the setting of single ventricle heart disease, results in hepatic injury and fibrosis over time. Fontan‐associated liver disease (FALD) is universally present in this cohort, and the current gold standard for diagnosis remains biopsy. Noninvasive assessments of liver fibrosis, such as ultrasound with elastography or acoustic radiation force impulse (ARFI), has been utilized in this cohort. The effect of poor cardiovascular efficiency, as measured by cardiopulmonary exercise test (CPET), on assessments of liver fibrosis remains poorly understood. Methods: Retrospective, cross‐sectional study. Subjects were evaluated in a multidisciplinary clinic setting for patients who have undergone Fontan operation. CPETs, liver ultrasound with elastography (ARFI), and standard laboratory tests were performed as part of routine clinical care pathway. Statistical analysis included linear correlation. Results: There was a poor correlation between mean ARFI velocity and peak oxygen consumption (VO2max ) in this cohort ( r = .20, P = NS). Similarly, there was poor correlation between ARFI and biomarkers of liver injury, time since Fontan operation and Fontan pressure. Discussion: ARFI had poor correlation with functional capacity after Fontan, as measured by VO2max obtained during CPET. While a single measurement of liver elastography was not associated with cardiopulmonary efficiency, longitudinal data may reveal an association.